Impact of Internet Banking Services on Customer Satisfaction in Nepalese Commercial Banks: A Study of Bardiya District - Acharya, Bhumi Raj; Tharu, Suman (Nepalese Journal of Management and Technology, 2025)
This study examines the impact of internet banking service adoption on customer satisfaction in Nepalese commercial banks, focusing on payment security, perceived ease of use, perceived credibility, and customer attitude as key determinants. A quantitative descriptive research design was employed, with data collected from 384 respondents through a structured questionnaire using convenience sampling. Data analysis was conducted using descriptive statistics, reliability testing, and multiple regression analysis. The findings reveal that internet banking services are generally perceived positively, with payment security emerging as the most significant predictor, followed by perceived ease of use and perceived credibility. The regression model explains a substantial proportion of variance in customer satisfaction, indicating strong explanatory power. However, customer attitude shows a positive but statistically insignificant effect. The study highlights the importance of secure, reliable, and user-friendly digital banking systems to enhance customer satisfaction and promote the growth of internet banking services in Nepal.